Soleus and Brachioradialis Muscles Modulationin APAs Recruitment Prior to Stand to Sit and Gait – A Pilot Study in Post Stroke Subjects - Silva, Augusta (2021)
Neural coupling, frequently impaired in post-stroke subjects, can be assessed through upper limb flexor components against gravitiy like the brachioradialis muscles activity. Based on the known infkuence of the lower limb activity in the upper limb motor behavior it can be raised the question on whether the dysfunctional modulation of the extensors also happens in the brachioradialis muscle.